Correlation Between Nutritional Status of Pregnant Women Based on Upper Arm Circumference and Preeclampsia/Eclampsia Severity Degree at Jagir Public Health Center During January 2014 - March 2014 - Dian Nirmala Aprilia; Budi Prasetyo; Sulistiawati Sulistiawati (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: Preeclampsia/eclampsia is one of the causes of maternal mortality besides bleeding and infection. The exact etiology of this condition is still unknown. Nutritional status of pregnant women who are overweight can increase the risk. This study aims to determine the correlation between obesity and the severity of preeclampsia/eclampsia through upper arm circumference (UAC) measurement.Methods: This study is a cross-sectional analytic study. Data on preeclampsia/eclampsia and UAC obtained from patient medical records in Jagir Public Health Center Surabaya. Data were analyzed using Chi-square test.Results: Prevalence of mild preeclampsia was greater than severe preeclampsia (87.5% and 12.5%). The majority of patients with mild preeclampsia have normal UAC size (91.3%). Severe preeclampsia found higher in obesity group than normal nutritional status group (22.2% and 9.1%). From Chi-square test analysis, found that p = 0.557.Conclusion: There was no significant correlation between the nutritional status of pregnant women based on UAC measurement of and the severity of preeclampsia/eclampsia.